Two-step mode of clay formation in the extensional basins: Cambrian–Ordovician clastic rocks of the Antalya unit, SW Turkey. (2nd January 2018) - Bozkaya, Ö.; Yalçin, H.; Schroeder, P.A.
Abstract: Ordovician clastic rocks of the Antalya unit in SW Turkey bear mineralogical/geochemical evidence of Triassic extensional rift timing and spatial relations. The crystal chemistry of the phyllosilicate assemblages (illite, chlorite, kaolinite, mixed-layer illite-smectite, chlorite-vermiculite and chlorite-smectite) is consistent with the rock experiencing a multi-generational burial history. The appearance of kaolinite and illite-smectite-bearing rocks in the Antalya unit is characteristic of diagenetic-anchimetamorphic conditions and is of higher grade than their anchi-epizonal equivalents in other regions of the Tauride belt. Illites and chlorites are of both detrital and authigenic origin, whereas I-S and kaolinites are authigenic. Detrital micas have been altered to chlorite and K-white mica stacks in which relicts suggest the chlorites were derived from detrital biotites. The broad X-ray diffraction illite peaks show that they are composed both of illite and illite-smectite. Na, K-mica and paragonite occur within the chlorite-mica stacks as replacements of muscovite, probably driven by Na-rich solutions. The authigenic clays were formed within the microporous matrix and the interplanar spaces of {001} planes of chlorite-mica stacks, with textures independent of the bedding and foliation planes of the rocks. The authigenic chlorites exhibit higher Si and Fe and lower Mg contents than their detrital counterparts. Authigenic chlorite thermometry indicates rift-related temperatures of 50–150°C, whereas pre-rift detrital chlorites formed at temperatures of  >200°C. Authigenic illite and illite-smectite are phengitic in composition and contain more Si, Mg, Fe and Ca and less Al and K than detrital K-white micas. The textural, mineralogical and chemical characteristics support the hypothesis that the mineral assemblages were a result of a two-step mode of formation with diagenetic overprints of previously anchizonal rocks in extensional basin conditions.